Contributions to the genus Bolbochromus Boucomont, 1909 (Coleoptera: Geotrupidae: Bolboceratinae) from China, with the description of a new species - Gao, Han; Geshev, Georgi A. (Zootaxa, 2025)
A new species of the genus Bolbochromus Boucomont, 1909, Bolbochromus sunfengyii Gao & Yang, new species, is described from Yunnan, China. The female of B. nomurai Li & Krikken, 2013 is described for the first time. Bolbochromus sinensis Krikken & Li, 2013 is newly recorded from Jiangxi and Zhejiang Provinces. Elytral color pattern variations of the aforementioned species are also provided.